Life cycle assessment of the existing and proposed municipal solid waste management system in Moscow, Russia. (15th December 2021) - Vinitskaia, Natalia; Zaikova, Anna; Deviatkin, Ivan; Bachina, Oksana; Horttanainen, Mika
Abstract: This study provides the first life cycle assessment (LCA) for municipal solid waste waste management system in one of the largest cities in Europe, Moscow. Its significance stems from recent important changes in the waste management system, the introduction of limited source separate collection in 2020, and the first examination of sorted municipal solid waste (MSW) composition. Moscow city generates 8.1 million tonnes of MSW per year, most of which is still mainly disposed of in landfill sites. The study assesses the current situation, the waste management system planned to be operational by 2024 and proposes improvements to separate collection and treatment of organic waste that could be adopted in the future. In this context, 6 scenarios are compared using LCA based approach. The impacts are presented as global warming potential (GWP), acidification potential (AP) and eutrophication potential (EP). The results show that the existing MSW management system has the highest GWP and AP. Planned changes to the system by 2024 will reduce impacts in all categories. The largest emissions reduction potential is found for refuse-derived fuel (RDF) production and its use in cement kilns as a replacement for coal, which reduces emissions by 1.1 kg CO2 -eq/kgRDF and results in a negative AP. The change in EP remains negligible. Separate collection and treatment of biowaste is also beneficial, with anaerobic digestion being the most advantageous treatment method. Nevertheless, even after the implementation of all initiatives, landfill still represents about 53% of direct emissions in GWP. Sensitivity analysis estimated that flaring of landfill gas can reduce GWP from landfill sites by a factor greater than two. With these changes, the total emissions of the system approach zero. Energy recovery at MSW incineration plants and substitution to the grid gives reductions in GWP and EP in the range of 35% and provides especially significant reductions in AP. The waste management system in Moscow accounts for 3% of residents' carbon footprint, which might drop to 1% if appropriate changes to the system are implemented. Highlights: RDF incineration, plastics recycling, avoided landfilling are key abetment methods. System changes and separate collection of biowaste can reduce GWP by 70%. Substitution of grid energy with that from waste and biogas should be prioritized. MSW management system of Moscow has a potential to reduce its GHGs to zero. The best-case scenario reduces GWP per capita by 230 kg CO2 -eq.